Upaya Peningkatan Disiplin Kinerja Guru Dalam Mewujudkan Mutu Pendidikan Berbasis Total Quality Management - Maharani Putri Kastari, Alisya; Destanty lubis, alvinna; Lydia Putri Tiatir, Jacqlien; Santy Yerkohok, Susana; Supriyanto, Achmad (Universitas Muhammadiyah Surakarta, 2024)
This research is based on the concepts and implications of efforts to improve the quality of education using a Total Quality Management (TQM) based approach, especially in the context of improving teacher performance discipline. This research aims to outline the importance of implementing TQM in improving the quality of education through increasing the discipline of teacher performance as well as identifying concrete solutions that can be taken to improve teacher performance in educational institutions. The research method used is a literature review study or literature study referring to the prism standard flow of searching for papers based on keywords from a website in the form of Google Scholar, Science Direct, and Emerald Insight. Then the researcher’s group with identification, screening and include stages then review the findings regarding TQM in schools and its impact on teacher work discipline and education quality. The results found that teacher performance discipline is a very important aspect in the educational context because it has a significant impact on the quality of education. However, there are still findings that there are irregularities in disciplinary practices carried out by teachers in a few educational institutions.